1998
DOI: 10.1016/s0550-3213(97)00737-2
|View full text |Cite
|
Sign up to set email alerts
|

Parton densities in a nucleon

Abstract: In this paper we re-analyse the situation with the shadowing corrections (SC) in QCD for the proton deep inelastic structure functions. We reconsider the Glauber -Mueller approach for the SC in deep inelastic scattering (DIS) and suggest a new nonlinear evolution equation. We argue that this equation solves the problem of the SC in the wide kinematic region where α S κ = α S 3πα S

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
80
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 47 publications
2
80
0
Order By: Relevance
“…It was also shown that the solution to the equation, suggested in Ref. [6], coincides with the solution to the GLR equation.…”
Section: Finding a Solution To This Equationmentioning
confidence: 66%
See 4 more Smart Citations
“…It was also shown that the solution to the equation, suggested in Ref. [6], coincides with the solution to the GLR equation.…”
Section: Finding a Solution To This Equationmentioning
confidence: 66%
“…The first one was suggested as an obvious generalization of pQCD approach [6] while the second has been obtained from semiclassical gluon field approach [7]. Both of them describe correctly the DGLAP [8] evolution in the limit of low parton density as well as the GLR nonlinear evolution equation [1] in the region of intermediate parton densities.…”
Section: Finding a Solution To This Equationmentioning
confidence: 99%
See 3 more Smart Citations